NOBLE GAS STUDIES IN CAIS FROM CV3 CHONDRITES: NO EVIDENCE FOR PRIMORDIAL NOBLE GASES - Vogel N.; Baur H.; Leya I.; Wieler R.; Bischoff A. (My University, 2004)
Calcium-aluminum-rich inclusions (CAIs) were among the first solids in the solar system and were, similar to chondrules, created at very high temperatures. While in chondrules, trapped noble gases have recently been detected, the presence of trapped gases in CAIs is unclear but could have important implications for CAI formation and for early solar system evolution in general. To reassess this question, He, Ne, and Ar isotopes were measured in small, carefully separated and, thus, uncontaminated samples of CAIs from the CV3 chondrites Allende, Axtell, and Efremovka. The 20Ne/22Ne ratios of all CAIs studied here are <0.9, indicating the absence of trapped Ne as, e.g., Ne-HL, Ne-Q, or solar wind Ne. The 21Ne/22Ne ratios range from 0.86 to 0.72, with fine-grained, more altered CAIs usually showing lower values than coarse-grained, less altered CAIs. This is attributed to variable amounts of cosmogenic Ne produced from Na-rich alteration phases rather than to the presence of Ne-G or Ne-R (essentially pure 22Ne) in the samples. Our interpretation is supported by model calculations of the isotopic composition of cosmogenic Ne in minerals common in CAIs. The 36Ar/38Ar ratios are between 0.7 and 4.8, with fine-grained CAIs within one meteorite showing higher ratios than the coarse-grained ones. This agrees with higher concentrations of cosmogenic 36Ar produced by neutron capture on 35Cl with subsequent β−-decay in finer-grained, more altered, and thus, more Cl-rich CAIs than in coarser-grained, less altered ones. Although our data do not strictly contradict the presence of small amounts of Ne-G, Ne-R, or trapped Ar in the CAIs, our noble gas signatures are most simply explained by cosmogenic production, mainly from Na-, Ca-, and Cl-rich minerals.